Towards a Psychoanalytic Concept of Affective-Digital Labour - Jacob Johanssen (Media and Communication, 2018)
This article draws on the argument that users on corporate social media conduct labour through the sharing of user-generated content. Critical political economists argue that such acts contribute to value creation on social media and are therefore to be seen as labour. Following a brief introduction of this paradigm, I relate it to the notion of affective labour which has been popularised by the Marxist thinkers Michael Hardt and Antonio Negri. To them, affective labour (as a sub-category of immaterial labour) denotes embodied forms of labour that are about passion, well-being, feelings of ease, immaterial products and generally a kind of communicative relationality between individuals. I point to some problems with a lack of clarity in their conceptualisation of affective labour and argue that the Freudian model of affect can help in theorising affective labour further through a focus on social media. According to Freud, affect can be understood as a subjective, bodily experience which is in tension with the discursive and denotes a momentary feeling of bodily dispossession. In order to illustrate those points, I draw on some data from a research project which featured interviews with social media users who have facial disfigurements about their affective experiences online. The narratives attempt to turn embodied experiences into discourse.